Creative process and aging in an action-research - Mendonça, Bruna Improta de Oliveira; Barreto Coutinho, Denise Maria (Revista de Psicología, 2019)
The purpose of this article is examining the effects of storytelling workshops with elderly in a situation of social vulnerability, participants of a NGO in Salvador, Bahia. The method was action-research. The analysis was based on repeated readings of the collected narratives, aiming at the construction of categories that emerged, from transcribed lines to corporal postures recorded in video. The reading of the transcriptions was conducted in the sense of grouping emergent and significant categories to be confronted with the state of the art on the subject. Among the results obtained, attention is drawn to some aspects: the promoting of a more engaged and inclusive participation; resignification of socially constructed stereotypes about old age; expansion of the critical sense and demands for more respectful living conditions; strengthening future life prospects and realizing personal projects; group integration and strengthening of ties, strengthening of memory; liberation of playfulness and creativity. Finally, we point to the relevance and effectiveness of this participatory research, in which all subjects involved are researchers and promoters of their own history and of creative emancipatory processes. It is possible to suppose that such intervention can be replicated with other groups, respecting specificities of each context.